Council of Europe: main characteristics and directions of activity in the budget sphere - Ivanova, Roksolana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The global acceleration and deepening of integration processes present modern states with the need to develop an optimal model of international legal interaction, which will make it possible to most effectively introduce foreign experience into the national legal system. Ukraine is no exception - the prospect of its integration into the European Union necessitates changes in various spheres of social life - political, economic, cultural, etc. However, it should be recognized: the central element of the mechanism of such rapprochement is law, and legal integration is a key form of European integration1. That is why an essential element of the further development of the legal system of Ukraine is the achievement of a certain level of consistency of the legislation of our country and the practice of its implementation with EU law.The Council of Europe, together with the states, continues to cooperate to ensure the effective implementation of the existing legal framework and strengthen the capacity of national institutions to harmonize national legislation and practice with European standards in order to promote human rights, strengthen the rule of law and ensure democratic principles of governance in the budgetary sphere.The action plan will focus on the effective implementation of the existing legislative framework, part of which was prepared within the framework of the previous ones. Such support will continue to be aimed at strengthening the capacity of relevant national institutions to function effectively. These capabilities include the ability to address gender issues and facilitate constructive dialogue between the government and civil society. The Council of Europe intends to gradually expand its coverage to the entire country, including the conflict-affected territories controlled by the authorities. Special emphasis will be placed on deepening coordination and interaction between national partners representing all branches of government, as well as between specialist groups and NGOs.